Ethical Violations in Patient-physician Relationship: A Survey from Kerman, Iran - Marzieh Khalilpour; Habibeh Ahmadipour; Mina Mobasher (Shiraz University of Medical Sciences, 2024)
Background: Although medical errors in the clinical system are a common cause of lawsuits against physicians, ethical violations have been reported at an alarming pace. We conducted this study to determine the frequency of ethical issues related to patientphysician relationships in registered complaints in three teaching hospitals in Kerman, Iran, from 2015 to 2018.Methods: In this cross-sectional study, we extracted data from all complaint cases registered in the complaints offices. The data were categorized according to ethical issues in the physicianpatient relationship including breaching confidentiality, not telling the truth to the patient, not obtaining informed consent, abandoning further treatment, causing unnecessary expenses, violating privacy, and not respecting the patient; then, we compared them according to our objectives using SPSS software.Results: The results showed that 51.7% of the physicians who had been sued were male, and 30.2% of all of them were general surgeons. The most common ethical issues were related to not respecting the patient (49.7%), abandoning further treatment (25.5%), not telling the truth to the patient (14.1%), and not obtaining informed consent (5.4%).Conclusion: The complaints received in three teaching hospitals can reveal the disregard for ethical codes, and irresponsible behavior among healthcare providers may endanger the patients' safety and increase the likelihood of injury in these hospitals. Further studies are recommended to determine the factors that influence ethical violation in the healthcare setting.